Analisis Kedisiplinan Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Aceh Singkil - Anis Tia; Sri Wayhu Handayani (UIR Press, 2022)
The purpose of this study is to analyze the performance discipline of the population and civil registration office of Aceh Singkil district, where discipline is very much needed in a government agency, especially agencies that interact directly with the community, discipline will be a big influence on employee performance in order to do work smoothly, good, and in accordance with established procedures. This research uses a qualitative method with a case study approach and uses primary techniques, data collection is directly in the field by observing techniques, interviewing employees of the population and civil registration services, secondary techniques based on books, previous research, including taking the required data from the population and civil registration office. The results of this research reveal the performance discipline that is carried out both in doing and completing work on time as needed by the community as a whole. so that people feel that the services provided are good, although they are still hampered by inadequate facilities and infrastructure, the employees try to provide quality services